Pemanfaatan Indole-3-Carbinol Sebagai Inhibitor Flavin Monooxygenase 3 (Fmo 3) Dalam Upaya Prevensi Aterosklerosis - Bagus Indra Kusuma; Brenda Desy Romadhon; Silvi Ahmada Chasya; Hazmi Dwinanda Nurqistan; Lusi Padma Sulistianingsih Mata (Jurnal Kardiologi Indonesia, 2015)
Cardiovascular disease is the leading cause of death in the world, reaching 30% of all mortality. The most common cause of cardiovascular disease is the formation of atherosclerotic plaque in blood vessels. Treatment has been done to overcome atherosclerosisonly curative and still no preventive. Processes that play a role in the formation of atherosclerotic plaque is very complex and one of the causes deposition of plaques is the formation of the compound trimethylamine oxide (TMAO) in the body. TMAO that has produced can increase the accumulation of cholesterol in macrophages so that increasing the formation of foam cells in the arterial wall. These compounds are derived from trimethylamine (TMA), which is converted into TMAO by enzyme flavin monooxygenase (FMO). FMO enzyme that is able to make an impact in the formation of TMAO is flavin monooxygenase 1 (FMO1) and flavin monooxygenase 3 (FMO3). However, FMO3 showed activity ten times greater than FMO1 in turning TMA into TMAO. Indole-3-carbinol can be a role for this enzyme inhibitor so that the therapeutic use of indole-3-carbinol is expected to inhibit TMAO. Therefore, the authors propose the use of research in the form of indole-3-carbinol as an inhibitor of flavin monooxygenase 3 (FMO3) in atherosclerosis prevention efforts. The study design used was pure experimental research design (true experimental design) with post test only randomized control group design. Mice (Mus musculus) males were treated indole-3-carbinol and then is given atherogenic diet for the provision of intravenous adrenaline 0.00084 mg / 20 gBW and egg yolks 0.2 cc / day. The treatment group consisted of a positive control, negative control, treatment A (10 mg / kg BW of indole-3-carbinol), B (200 mg / kg BW I3C), and C (500 mg / kg BW I3C). The data observed in the form of cholesterol, foam cell histopathological picture of the aorta and the density of the band FMO3 activity. Blood cholesterol levels showed a decrease in accordance with increase in dose. Cholesterol control of negative group, positive, A, B and C respectively of 119.4 ± 28.94 mg / dL, 246 ± 8.52 mg / dL, 224 ± 15.30 mg / dL, 170.6 ± 12.54 mg / dL, and 154.8 ± 14.46 mg / dL (p <0.05). Histopathologic features foam cell in the aorta of mice showed an improvement with the increase in dose. FMO3 enzyme activity also showed a decrease when compared to the positive control in the optical density relative scale along with rising doses of indole-3-carbinol given. This shows that the use of indole-3-carbinol is very effective in atherosclerosis prevention efforts.